Studies and global perspectives of second language teaching and learning - Schwieter, John W. (Research in second language learning., 2013)
This book explores theories and pedagogies in the L2 classroom that have led to an understanding of how non-native languages are taught and learned. Featuring a diverse set of perspectives from researchers and language educators from around the globe, this book highlights important theoretical and practical underpinnings of the L2 classroom--discussions on what has worked and why. Some examples of these topics include: online and nonverbal communication, peace literacy, learning behaviors, high-impact practices, pragmatic awareness, study abroad, implicit and explicit teaching, motivation, and more.One mission of this book is to appreciate a diverse array of L2 teaching practices with sound theoretical underpinnings and universal implications for L2 classrooms. The chapter contributions are the result of an open call for studies that highlight practical innovative approaches in L2 teaching and learning and expand the avenues of exploration available within their theoretical frameworks. More specifically, the call for proposals sought to gather a diverse set of perspectives from researchers and language educators from various parts of the world in order to provide practical and thought-provoking insight on innovative approaches to L2 teaching. As such, the studies in this book all share a common goal that demonstrates the applicability of L2 teaching practices across languages, cultures, and regions. The book is intended to act as a valuable reference for language educators, practitioners, specialists, and anyone studying or wishing to gain an overview of successful teaching practices and learning nuances in the L2 classroom that cross all languages, cultures, and regions.